THE ROLE OF WOMEN IN IMPROVING WELL-BEING FAMILY PERSPECTIVE MAQASHID SYARIAH - Muhamad Hasan Sebyar (Hukum Islam, 2021)
The participation of women in the world of work has not only contributed to changing the mindset and economic structure of a region, but has also contributed greatly to family welfare. This research uses descriptive analysis method to analyze and describe the role of women in improving the economic welfare of the family in the perspective of maqashid syariah. Based on the results of the research, it is found that the implication is that the role of women is very positive in improving family welfare and in accordance with the goals of Islam, namely falah (prosperous in the world and the hereafter), and according to the five main elements that must be maintained in Islam, namely hifz ad-din, hifz. an-nafs, hifz al-aql, hifz an-nasl, and hifz al-mall.